Diagnostic significance of suppressor of cytokine signalling 3 (SOCS3) methylation and its correlation with IDH1 mutation in Chinese glioma patients. (16th November 2016) - Jiao, Weili; Xun, Xiaojie; Liu, Jinhui; Yang, Jianhui; Wang, Qi; Wang, Lin; Chen, Chao; Wang, Huijuan; Dai, Penggao
Abstract: Context: Epigenetic alterations in suppressor of cytokine signalling 3 ( SOCS3 ) have been suggested as a potential biomarker in glioma. Objective: To investigate whether SOCS3 methylation could act as a biomarker for glioma grading and prognosis. Materials and methods: Glioma samples were evaluated by pyrosequencing and quantitative reverse transcription-polymerase chain reaction (qRT-PCR). Results: SOCS3 promoter methylation was more frequent in the WHO III and (anaplastic) oligoastrocytomas group. SOCS3 methylation status was significantly inversely correlated with mRNA expression level. Mutant IDH1 caused marked increase in SOCS3 methylation. Conclusion: SOCS3 methylation is a potential biomarker for grading and prognosis in human glioma.